Oxford Handbook of Accident and Emergency Medicine, 2nd Edition - Wyatt, Jonathan P., Illingworth, Robin N.; Clancy, Michael J.; Munro, Philip T.; Robertson, Colin E. (OXFORD UNIVERSITY PRESS, 2005)
It is impossible to over-emphasize the crucial nature of note-keeping in A&E. An average junior doctor or nurse will be involved directly in the treatment of up to 3000 new patients during a 6 month period. With the passage of time, it is impossible to remember all aspects relating to these cases, but there may be a requirement to give evidence in court, several years after the initial event. The only reference will be the notes made much earlier. Medicolegally, the A&E record is the prime source of evidence in medical negligence cases (p30). The defence organizations have in the past had to settle cases in which the notes were deficient and because, with the passage of time, the individual could not be clear about the details of a specific patient. A court may consider the standard of a doctor/nurse's notes to reflect his or her general standard of care. Sloppy, illegible or incomplete notes reflect badly on the individual. In contrast, if notes are neat, legible and detailed, those reviewing the case will naturally expect the doctor's general standards of care, in terms of history taking, examination and level of knowledge, to be competent. The Data Protection and Access to Medical Records Acts give patients right of access to their medical notes. If, whenever writing notes, you remember that the patient may in the future read exactly what you have written, then ill-advised, judgemental or rude comments are likely to be avoided. Follow the basic general rules listed below: Layout Follow a standard outline: Presenting complaint Indicate from whom the history has been obtained (eg the patient themselves, a relative, or ambulance personnel). Avoid attributing events to certain individuals (eg patient was struck by ‘Joe Bloggs’). Previous relevant history Especially note recent A&E attendances. Include family and social history. For example, an elderly woman with a Colles’ fracture of her dominant hand may be able to manage at home with routine follow-up provided she is normally in good health and has good family or other support. If, however, she lives alone in precarious social conditions without such support, then admission on ‘social grounds’ may be required. Current medications Remember to ask about non-prescribed drugs (including recreational, herbal and homeopathic). Some women may not volunteer the OCP as a ‘medication’ unless specifically asked. Enquire about allergies to medications, and document the nature of this reaction. Examination findings As well as +ve features, document relevant -ve findings (eg the absence of neck stiffness in a patient with headache and pyrexia). Always document the side of the patient which has been injured. For upper limb injuries note whether the patient is right or left-handed. Document if a patient is abusive or aggressive, but avoid non-medical, judgemental terms, (eg ‘drunk’). Use ‘left’ and ‘right’, not ‘L’ and ‘R’. Investigation findings Record clearly. Working diagnosis For patients who are being admitted, this may be adifferential diagnostic list. P.3